Perbaikan Tata Letak Mesin dengan Metode Systematic Layout Planning (SLP) di PT Prisma Rekayasa Unggul - Suryatman, Tina Hernawati; Kosim, Muhamad Engkos; Ricardo, Ricardo; Muttaqien, Zaenal (Journal Industrial Manufacturing, 2024)
PT. Prisma Engineering Unggul is an engineering company and manufacturer of engineering transportation equipment, designing and manufacturing engineering products specifically for off-road applications used in the mining, oil and gas, agroforestry and transportation sectors. Production machine layout at PT. Prisma Engineering Unggul has not followed the layout of the production area in accordance with the flow of the material handling process. So the machines are still very close together or far apart, so that a lot of materials and products are scattered about in the wrong place, causing buildup and making it difficult to walk in the production area. Objectives To find out the best spacing layouts for arranging production machines using the systematic layout planning (SLP) method and ARC (Activity Relationship Chart),ARD (Activity Relationship Diagram tools using field study methods, linear studies, brainstorming (brainstorming/feedback). Based on the method (SLP) can determine the relationship between the activities of the relationship between machines can produce machine layout to be based on production flow. For the proposed layout of the machine distances that have been made, it can be seen that the machines are neater in sequence with the flow of material. So that the activity of moving material is lower and the total time is relatively short, production results can also be placed not scattered and make it easier to walk in the production area.Keywords : SLP, ARC, ARD, Layout, Machine Distance.